Gambaran Pengetahuan dan Perilaku Merokok pada Siswa di SMKS Garudaya Bontonompo - Rizki Ikrayanti; Fanny Dewi Sartika; Andi Budiyanto Adi Putra (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2025)
During adolescence, students are often exposed to various risk behaviors, one of which is smoking. Smoking among adolescents can be influenced by various factors, including social environment and peer pressure. This study aims to describe the knowledge and smoking behavior of 12th-grade students at SMKS Garudaya Bontonompo, Gowa Regency. The research method used is descriptive quantitative with a survey approach, involving 64 students as respondents selected randomly. Data were collected using a validated questionnaire and analyzed descriptively. The results showed that most students had good knowledge about the dangers of smoking, but smoking behavior remained high. Of the 64 students, 59% had good knowledge about smoking, but 81% still smoked. Factors influencing smoking behavior include peer influence, social environment, and social interactions. The results of this study highlight the need for more intensive health education interventions in schools to increase students' awareness of the dangers of smoking and to encourage more positive behavioral changes.